Intergenerational Disadvantage: Learning about Equal Opportunity from Social Assistance Receipt - Deborah A. Cobb-Clark; Sarah C. Dahmann; Nicolás Salamanca; Anna Zhu (Institute of Labor Economics (IZA), 2017)
We use variation in the extent of generational persistence across social assistance payments to shed light on the factors leading to intergenerational disadvantage. Our administrative data come from the Australian social security system and provide us with detailed social assistance trajectories – across the entire social safety net – for a birth cohort of young people and their families over an 18-year period. We find that young people are 1.8 times more likely to need social assistance if their parents have a history of receiving social assistance themselves. These young people also receive more intensive support; an additional 12,000 over an 8-year period. The intergenerational correlation is particularly strong in the case of disability payments, payments for those with caring responsibilities, and parenting payments for single parents. Disadvantage stemming from parents' poor labor market outcomes seems to be easier for young people to overcome. This suggests that parental disadvantage may be more harmful to children's later life outcomes if it is more strongly driven by circumstances rather than personal choice.
Keywords: H53; I38; J62; 330; intergenerational correlations; socioeconomic disadvantage; social assistance